2011
DOI: 10.1074/jbc.m111.251736
|View full text |Cite
|
Sign up to set email alerts
|

Endo-β-1,3-galactanase from Winter Mushroom Flammulina velutipes

Abstract: Arabinogalactan proteins are proteoglycans found on the cell surface and in the cell walls of higher plants. The carbohydrate moieties of most arabinogalactan proteins are composed of ␤-1,3-galactan main chains and ␤-1,6-galactan side chains, to which other auxiliary sugars are attached. For the present study, an endo-␤-1,3-galactanase, designated FvEn3GAL, was first purified and cloned from winter mushroom Flammulina velutipes. The enzyme specifically hydrolyzed ␤-1,3-galactan, but did not act on ␤-1,3-glucan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 48 publications
3
28
0
Order By: Relevance
“…Studies have also reported isolation of proteins such as hemagglutanin which has mitogenic and antiproliferative functions, ice binding proteins and also the flammutoxin as a cytolysin (Tadjibaeva et al, 2000; Ng et al, 2006; Raymond and Janech, 2009). In addition, proflamin, a glycoprotein enzyme with anticancer activity, and asparaginase were also discovered in the mycelium of the mushroom (Maruyama and Ikekawa, 2007; Eisele et al, 2011; Kotake et al, 2011). …”
Section: Chemical Composition and Nutritional Value Of F Velutipesmentioning
confidence: 99%
“…Studies have also reported isolation of proteins such as hemagglutanin which has mitogenic and antiproliferative functions, ice binding proteins and also the flammutoxin as a cytolysin (Tadjibaeva et al, 2000; Ng et al, 2006; Raymond and Janech, 2009). In addition, proflamin, a glycoprotein enzyme with anticancer activity, and asparaginase were also discovered in the mycelium of the mushroom (Maruyama and Ikekawa, 2007; Eisele et al, 2011; Kotake et al, 2011). …”
Section: Chemical Composition and Nutritional Value Of F Velutipesmentioning
confidence: 99%
“…On the contrary, b-galactans III and IV, which have a high proportion of b-1,3-galactan, exhibited significantly higher reactivity than native gum arabic and b-galactan I based on sugar weight. Yariv reactivity of b-galactan IV was lost by treatment with endo-b-1,3-galactanase from winter mushroom (Flammulina velutipes), FvEn3Gal (Kotake et al, 2011). b-Galactan IV also failed to interact with a-Gal-Yariv (Supplemental Fig.…”
Section: Effect Of the Removal Of B-16-galactan Side Chains On Yarivmentioning
confidence: 99%
“…The content of uronic acid was measured by a modified carbazole-sulfuric acid method (Galambos, 1967). In the hydrolysis of b-galactan IV and b-1,3-Gal 9 , recombinant FvEn3Gal was used (Kotake et al, 2011).…”
Section: Trimming Of Agpmentioning
confidence: 99%
“…42,45,46 The CAZy database (http://www.cazy.org/) 50 classifies glycoyl hydrolases into 130 families based on amino acid sequence similarities. Recently, Kotake et al 40 reported on the isolation of an endo -β-(1→3)-Dgalactanase from the mushroom, Flammulina velutipes . Sequence information and phylogenetic analysis determined that this enzyme belongs to CAZy GH 16, a family containing other endo -acting enzymes, including endo -β-(1→3)- and endo -β-(1→3, 1→4)- glucanases.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is only one report to date of the isolation of an endo -β-(1→3)-D-galactanase. 40 Enzymes may have different modes of action and/or catalytic sites. It is therefore important to isolate a wide spectrum of hydrolytic enzymes that cleave specific glycosyl linkages of the type II AGs.…”
Section: Introductionmentioning
confidence: 99%